A utilização do Facebook como recurso auxiliar à experiência filosófica no ensino médio: uma alternativa de aplicação da metodologia de Sílvio Gallo - Freitas, Jossilane de Sousa (2020)
The present study it aims to present the construction and analyze the viability of an alternative philosophy teaching practice that combines the methodological proposal of the educator and philosopher Sílvio Gallo with the virtual environment of one of the most used social networks in Brazil and in the world. In this perspective, Facebook acquires, in the investigation, the function of auxiliary and complementary tool to the development of Philosophy classes, which allowed us, through its adaptation and adequate configuration, to think about an experience and methodological application of the teaching of Philosophy. For the development of the work, we start from its construction and theoretical foundation, which qualifies it in principle as a bibliographic research. Thus, at first, readings and analyzes were made on the methodological and teaching proposal of Philosophy defended by Sílvio Gallo, as well as we used other references that meet the thinking adopted by our main author. We also use academic research and data that point to the viability and contribution of virtual spaces in the educational process. In a second stage, the research acquires its exploratory and descriptive character, that is, we started the process of analysis, presentation and exploration of the social network in order to identify which resources, functionalities and configurations are most suitable for the use of Facebook in the teaching of philosophy. At that moment, we present the product of our research proposal, that is, we build and organize information and guidelines similar to a step by step with models that exemplify and clarify how each step, not only of creating and configuring the environment, but also how methodological moments proposed by Gallo, namely awareness, problematization, research and conceptualization can be developed and applied in the process of appropriation and use of the referred virtual environment. In our final remarks, we highlight the great potential and show the feasibility of using Facebook as an auxiliary resource for teaching philosophy, recognizing it as capable, from its correct adaptation and configuration, to provide the development of essential characteristics to philosophical thinking in high school.